Research on the Assets Sharing Economy of Colleges and Universities under the Background of the Digital Economy — From the Perspective of Transaction Costs - Zhu, Xiaohong (Journal of Global Economy, Business and Finance, 2025)
Grounded in Williamson’s transaction cost economics and situated within the current implementation of integrated budget management platforms, this study systematically investigates the theoretical logic and institutional innovation pathways underlying asset sharing in colleges and universities during the digital economy era. Digital technologies substantially reduce institutional transaction costs in asset sharing by reconfiguring three core dimensions: asset specificity, transaction uncertainty, and transaction frequency. The broad deployment of integrated budget management platforms offers standardized and operationally robust technical infrastructure, which effectively curtails information search and contract enforcement costs. At the same time, the in-depth advancement of digital asset management in colleges and universities, through the organic integration of smart contracts and credit evaluation systems, effectively alleviates the sharing dilemma caused by the specificity nature of colleges and universities assets. This study not only extends the applicability of transaction cost theory to public resource allocation but also offers theoretical and practical insights for enhancing the allocation efficiency and utilization effectiveness of assets in colleges and universities.